Future of the CAP in the new Financial Perspective 2014-2020. Challenges and Consequences for Poland - Czyżewski, Andrzej; Poczta-Wajda, Agnieszka (Publishing House of the Wrocław University of Economics, 2009)
Since the beginning of the European Communities (EC) the Common Agricul-tural Policy (CAP) has been one of the most important fields of economic co-operation among Member States, which can be proved, among others, by relatively high share of agricultural expenditures in the EU budget.1 During the first 50 years of its existence the CAP remained unchanged. The process of the CAP reforms first started in the last 15 years. This policy was criticized because of its high costs, creating tidy food surpluses and the growing concentration of agricultural support in a few beneficiaries, mainly large-area farms. The level of agricultural support of the EU was also strongly criticized on the international arena, especially within the negotiations of the World Trade Organization (WTO). In the conditions of growing economic welfare and the food security it was more and more difficult to find social justification for the strongly protective agricultural policy. The picture of the CAP became even more complicated after 10 new countries joined the EU in 2004 and another 2 in 2007. The impact of the latest EU enlargement on the agricultural sector is enormous. Labour resources increased from 6 million to 13 million people and farm land resources grew from 130 million to 180 million hectares. However, the level of income on the rural areas of the new Member States is lower and the rate of unemployment higher, which creates a new challenge for agricultural policy of the EU. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 98-108